FINANCIAL HELP SEEKING BEHAVIOR PADA MAHASISWA DI SURABAYA - Stephen Geraldo; Evelyn Evelyn (Universitas Mercu Buana, 2020)
The purpose of this study is to identify the factors that influence financial help-seeking behavior among university students in Surabaya. The study was conducted by distributing questionnaires to undergraduate and graduate students in Surabaya. Data analysis was performed with logistic regression. Help seekers tend to have less financial education, negative financial behavior, higher financial risk tolerance, higher levels of financial stress, and low financial self-efficacy. The results of this study are expected to help the concerned parties to formulate various policies that can improve one's financial welfare, in this case, university students.